The factors that influence individual contribution towards zakat income in Negeri Sembilan / Ahmad Nur Hamizan Rasip - Rasip, Ahmad Nur Hamizan (Faculty of Business and Management, 2015)
“THE FACTORS THAT INFLUENCE INDIVIDUAL CONTRIBUTION TOWARDS ZAKAT INCOME IN NEGERI SEMBILAN” is conducted as partial requirement to fulfil the requirement as needed by the faculty of Business Management, MARA University of Technology (UITM). The intention of this study is to determine the factors that influence individual contribution towards zakat income. The researchers chose to use descriptive research design as a method to conduct this study and survey in order to gain the data. Data used in this research are primary and secondary data such as journal and books. Researcher also use questionnaire to attain the data in order to get the feedback from the zakat payers around Negeri Sembilan.